(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
In case of hanging the process of respiration i.e. the exchange of air between the atmosphere and the alveoli of lungs is prevented by ligature in neck, leading to asphyxia and death. Hanging may be complete/incomplete (partial) where the constricting forces are the body weight or even only the weight of the head. In complete hanging whole body is suspended, no part of the body touches the ground. Complete hanging is suicidal in nature unless otherwise proved. In partial hanging any part of the body touches the ground. Partial hanging is suicidal (100%) in nature & there is no 2nd thought. Generally Medical and non-medical personals think that complete hanging may be suicidal, but partial hanging is definitely homicidal in nature which is not the actual fact. Hanging with signs of torture in various parts of body goes in favour of (provoked) suicidal nature. DOI: http://dx.doi.org/10.3329/jdnmch.v18i1.12244 J. Dhaka National Med. Coll. Hos. 2012; 18 (01): 63-64